Policy styles, opportunity structures and proportionality: Comparing renewable electricity policies in the UK. Issue 1 (January 2021) - Leiren, Merethe Dotterud; Inderberg, Tor Håkon Jackson; Rayner, Tim
Researchers expect under-reaction in climate policy. However, this might differ depending on the access of different interest groups to a political system. To explore the relationship between entrenched patterns of domestic politics and proportionality of climate policy, we compare two renewables policies which financially support new renewable electricity in the UK. Drawing on the literature on policy styles and related opportunity structures, this article shows that UK political parties have responded to growing public concern and NGO pressure by, at times, trying to out-green one another to win votes. However, powerful industry actors have been influential in shaping UK renewables policies, in particular when political competition about the individual policies has been low. The findings suggest that an over-reaction in terms of exceeding the marginal costs of renewable electricity production is equally likely under conditions of high or low political competition.